2017
DOI: 10.1161/jaha.117.006580
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Baseline Serum Fibrinogen: Effect on 2‐Year Major Adverse Cardiovascular Events Following Percutaneous Coronary Intervention

Abstract: BackgroundElevated fibrinogen is associated with short‐term major adverse cardiovascular events (MACE) after percutaneous coronary intervention, but the relation with late MACE is unknown.Methods and ResultsBaseline demographics and 2‐year MACE were recorded among subjects undergoing nonemergent percutaneous coronary intervention. A total of 332 subjects (66.6±19.5 years, 69.9% male, 25.3% acute coronary syndrome) were enrolled. Two‐year MACE (periprocedural myocardial infarction 9.0%, rehospitalization 6.3%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 25 publications
5
34
0
2
Order By: Relevance
“…Fibrinogen (Fib), as a thromboplastic and inflammatory marker, facilitates blood viscosity, platelet aggregation, fibrin cross-linking, and plays a pivotal role in the progression of atherosclerosis [1,2]. Previous studies showed that Fib was not only an indicator of subclinical cardiovascular diseases, such as coronary artery calcification and intima-media thickness of the carotid artery [3,4], but was also independently associated with the development of coronary artery disease (CAD), hypertension, stroke, as well as adverse cardiovascular events [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Fibrinogen (Fib), as a thromboplastic and inflammatory marker, facilitates blood viscosity, platelet aggregation, fibrin cross-linking, and plays a pivotal role in the progression of atherosclerosis [1,2]. Previous studies showed that Fib was not only an indicator of subclinical cardiovascular diseases, such as coronary artery calcification and intima-media thickness of the carotid artery [3,4], but was also independently associated with the development of coronary artery disease (CAD), hypertension, stroke, as well as adverse cardiovascular events [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Previous studies have shown that fibrinogen was not only independently associated with the development of CAD, hypertension and stroke, but also an independent predictor of long-term prognosis in patients after PCI. [12][13][14] More recently, it has been reported that the D-dimer to fibrinogen ratio (DFR) is a novel predictor for the outcomes of pulmonary thromboembolism (PTE), ischemic stroke and gastrointestinal stromal tumors (GISTs). [15][16][17] However, the relationship between the DFR and prognosis in CAD patients after PCI has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike apolipoprotein B, apo(a) does not contain lipid domains or transport lipid, but instead, it potentiates atherothrombosis through additional pathways including proin ammatory, and potentially anti brinolytic effects by inhibiting plasminogen activation [10]. As one of the important components of brinolytic system, plasma brinogen (Fib) has been proved to be a pivotal CVD risk factor [11][12][13]. However, little is known about the inter-relationship of Lp(a) and Fib in the CVEs risk prediction in the secondary prevention setting.…”
Section: Introductionmentioning
confidence: 99%